Exploring the Role of Pharmacists in Improving Medication Adherence among Diabetic Patients in Primary Healthcare Facilities - Fef Rukminingsih; Bayu Dwi Handono (PT FORMOSA CENDEKIA GLOBAL, 2026)
Non-adherence to medication among patients with diabetes mellitus remains a major challenge in primary healthcare due to its impact on disease control and complications. This study aimed to explore the role of pharmacists in improving medication adherence through pharmaceutical counseling in two primary healthcare facilities in Semarang, Central Java. Using an exploratory qualitative approach, data were collected from nine purposively selected informants through in-depth interviews, observation, and document analysis. The findings revealed that pharmacists improved medication adherence through structured education, individualized counseling, therapy clarification, and motivational support. However, limited counseling time and variations in patient health literacy remained significant barriers. In conclusion, pharmaceutical counseling plays an important role in improving medication adherence and should be strengthened through healthcare system and policy support.